Non-genital warts among primary school students in Bilkas District, Egypt: prevalence and associated factors - El-Gilany, Abdel-Hady (Journal of Pakistan Association of Dermatologists, 2022)
Abstract Background: warts are common skin disease among children and adolescent due to various behavioral, environmental and hygienic factors. This study aims to estimate the prevalence of non-genital warts and its associated risk factors in primary school students in Bilkas District, Egypt Methods: A cross-sectional study was done on 1304 primary schools students. Data collected included sociodemographic characteristics and hygienic practices. Students were clinically examined for presence of warts, their number, site, duration and history of recurrence. Cases were referred for treatment at Dermatology clinic, Mansoura University Hospital. Results: About 10% of students had one or more non-genital warts. The logistic regression analysis revealed that the independent predictors of presence of warts, were low and middle socioeconomic status (AOR=14.5 and AOR=8.7; respectively), students in rural residence (AOR=2.5), students sharing shoes (AOR=2.8) and students from grade 1 to 3 (AOR=2.1). Conclusion: The prevalence of non-genital warts was relatively high among primary school students in Bilkas district. The risk is higher in low and middle socioeconomic status, rural residence and sharing shoes. Health education about the simple preventive measures and personal hygiene is important.